Improving Digital Marketing Skills of MSMEs in Legok Village through a Community Service Program - Fahmy Rinanda Saputri; Melissa Indah Fianty; Marojahan Tampubolon (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
There are several problems in marketing the products of Micro, Small and Medium Enterprises (MSMEs) in this digital era. Problems such as limited access to technology and lack of knowledge and expertise in managing digital platforms or tools. To overcome these problems, Community Service (PKM) activities are carried out. This PKM is focused on improving marketing skills for MSME players in Legok Village, Tangerang, Banten by Universitas Multimedia Nusantara (UMN). Specifically, this solution is in the form of training with the theme of digital marketing management, market trend analysis, customer preferences, and strategies to increase customer interaction on e-commerce platforms and social media. The materials in this PKM activity are market trend analysis and the use of digital marketing tools where there are 19 participants from different MSME players. The results of this training showed that 100% of participants stated that the training delivered provided new insights or ideas to improve their business, especially in terms of marketing management. Thus, MSMEs in Legok Village are expected to be able to compete better in the digital market, which in turn can encourage local and national economic growth.